2020
DOI: 10.3389/fncel.2020.00056
|View full text |Cite
|
Sign up to set email alerts
|

Experience-Dependent Changes in Myelin Basic Protein Expression in Adult Visual and Somatosensory Cortex

Abstract: An experience-driven increase in oligodendrocytes and myelin in the somatosensory cortex (S1) has emerged as a new marker of adult cortical plasticity. That finding contrasts with the view that myelin is a structural brake on plasticity, and that contributes to ending the critical period (CP) in the visual cortex (V1). Despite the evidence that myelin-derived signaling acts to end CP in V1, there is no information about myelin changes during adult plasticity in V1. To address this, we quantified the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Recent data suggest that MBP regulation may not even reflect synaptic plasticity in general. In mouse SC, MBP is regulated by environmental enrichment even weeks after birth with enrichment promoting the integration of newly myelinating oligodendrocytes, whereas in VC MBP is regulated by visual activity and decreases upon visual deprivation (Hughes et al 2018 ; Murphy et al 2020 ). Areal differences already exist at the progenitor level because proliferation of NG2 positive OPCs can be enhanced in mouse barrel cortex after whisker lesion, but not in visual cortex after dark rearing (Mangin et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that MBP regulation may not even reflect synaptic plasticity in general. In mouse SC, MBP is regulated by environmental enrichment even weeks after birth with enrichment promoting the integration of newly myelinating oligodendrocytes, whereas in VC MBP is regulated by visual activity and decreases upon visual deprivation (Hughes et al 2018 ; Murphy et al 2020 ). Areal differences already exist at the progenitor level because proliferation of NG2 positive OPCs can be enhanced in mouse barrel cortex after whisker lesion, but not in visual cortex after dark rearing (Mangin et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experience-dependent myelin plasticity affects both visual and somatosensory systems. Monocular deprivation of one eye in adult rats decreases markers of myelination in the related hemisphere of the visual cortex, whereas the non-deprived hemisphere exhibits the opposite (Murphy et al, 2020). This suggests that myelin adapts to the changing balance of cortical neuronal activity.…”
Section: Sensory Experiencementioning
confidence: 93%
“…Many literatures have shown that the brain responds to experience-induced activities [ 30 33 ] and environmental changes [ 34 , 35 ]. Changes in myelin sheaths, neurons, and synapses can be observed both in animal and cell culture models.…”
Section: Effect Of Enriched Environment On Myelinationmentioning
confidence: 99%